Exploring Indonesian Learners’ Attitudes and Beliefs toward English Accents: A Case Study in an Indonesian University - Dewianti Khazanah (Journal of English Language Teaching and Linguistics, 2023)
This study reported the attitudes of 67 Indonesian English language learners toward British, American, and their own English accents and explored the underlying reasons motivating these attitudes. The participants’ English proficiency ranged from intermediate to advanced proficiency and confirmed either or both direct and indirect exposures to intercultural communication with speakers of English of other nationalities. The participants were required to listen to three audio samples, Received Pronunciation (RP), General American (GA), and Indonesian accented English (IAE), and to rate the accents on ‘standard’, ‘intelligent’, ‘polite’, and ‘pleasant’ traits. To seek the significant overall mean scores and the meaningful scores across the groups, ANOVA and post-hoc Tukey test were used. The results of the interview, additionally, were analyzed using content analysis techniques to find meaningful categories to clarify such emerging perceptions. The results show an overall positive attitude toward all three accents with the Indonesian accent perceived significantly more positively compared to the other two on the ‘intelligent’, ‘polite’, and ‘pleasant’ traits. The more positive evaluation of their own accent was driven by the realization that mutual intelligibility is more important than prestige, and there is a need for cultural value projections, that is, to use their own accent to channel politeness. These results call for the reinforcement of mutual intelligibility as the core of assessment and acceptance of local accents in classrooms. This can be channeled through the active promotion of audio samples demonstrating different varieties of English in the class instead of focusing exclusively on RP and GA; and through teachers’ acceptance of students’ intelligible local accents.